A Case of Burr Hole Drainage and Middle Meningeal Artery Embolization for Chronic Subdural Hematoma Associated with Spontaneous Intracranial Hypotension - Shimoi, Akihiro; Kowata, Kazuma; Yoshida, Keisuke; Takahashi, Hironori; Akaji, Kazunori (Asian Journal of Neurosurgery, 2025)
Idiopathic intracranial hypotension (IIH) is an uncommon condition characterized by cerebrospinal fluid leakage, which may lead to complications such as chronic subdural hematoma (CSDH). Management of recurrent CSDH in the context of IIH remains a therapeutic challenge. A 50-year-old man presented with bilateral CSDH associated with symptoms of IIH. Initial conservative treatment was followed by burr hole drainage due to deteriorating consciousness. Despite temporary improvement, hematoma recurrence necessitated repeat drainage. Subsequently, bilateral middle meningeal artery embolization (MMAE) was performed. The patient showed rapid clinical recovery, and no recurrence was observed at 3-month follow-up. MMAE may be an effective and minimally invasive treatment option for recurrent CSDH associated with IIH, especially when surgical intervention poses risks or proves insufficient. Early recognition of IIH and tailored intervention strategies are essential for optimal outcomes.
Keywords: burr hole drainage; chronic subdural hematoma; intracranial hypotension; middle meningeal artery embolization; hematoma